2017
DOI: 10.1111/iju.13472
|View full text |Cite
|
Sign up to set email alerts
|

Age and prostate volume are risk factors for transient urinary incontinence after transurethral enucleation with bipolar for benign prostatic hyperplasia

Abstract: Objectives: To investigate the predictive factors for transient urinary incontinence after transurethral enucleation with bipolar. Methods: We retrospectively analyzed the data of 584 patients who underwent transurethral enucleation with bipolar between December 2011 and September 2016 operated by a single surgeon. Urinary incontinence after transurethral enucleation with bipolar was defined as involuntary leakage of urine that required the use of pads. It was evaluated at 1 week, and 1, 3, 6, 12 and 24 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…investigated the relationship between PV and the incidence of stress urinary incontinence after HoLEP, and discovered that large prostate size is associated with longer operative time and longer time of manipulation with the sheath across the external sphincter during HoLEP 12 . Other previous reports suggested that the damage to the urethral sphincter as a result of prolonged operation times was one of the causes of postoperative TUI; they emphasized the importance of reducing operation times 13,15,22 . The present results were consistent with their reported findings.…”
Section: Discussionsupporting
confidence: 91%
“…investigated the relationship between PV and the incidence of stress urinary incontinence after HoLEP, and discovered that large prostate size is associated with longer operative time and longer time of manipulation with the sheath across the external sphincter during HoLEP 12 . Other previous reports suggested that the damage to the urethral sphincter as a result of prolonged operation times was one of the causes of postoperative TUI; they emphasized the importance of reducing operation times 13,15,22 . The present results were consistent with their reported findings.…”
Section: Discussionsupporting
confidence: 91%
“…35 The majority of PKEP is performed bluntly using the tip of the resectoscope or electrode, 10 and this mechanical dissection will stretch the inner longitudinal layer around the apex of prostate, and might result in transient injury to the urethral sphincter complex and surrounding structures. 36 Considering that the neurovascular bundle runs only 3 mm from the apical prostate capsule, and 3 to 4 mm from the membranous urethral lumen, 37 further studies are needed to comprehensively evaluate the potential impact of mechanical enucleation on EF.…”
Section: Discussionmentioning
confidence: 99%
“…Although UI is defined differently in different literature which is one of the limitations when comparing UI, most study defined UI after AEEP as involuntary leakage of urine that required the use of pads (Hirasawa, Kato, & Fujita, ). There were several causes of UI, including dysfunction of the bladder and urethra, intra‐operative injury to the external sphincter of the urethra, prolonged retention catheterisation, local infection or oedema of the prostatic fossa and urethra (Hirasawa et al, ; Nojavan et al, ; Sapetti et al, ). Different types of post‐operative UI could occur in patients with BPO, including transient UI, permanent UI, stress UI, urgency UI, mixed UI and so on.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…It is reported that the incidence of post‐operative UI could be reduced significantly after 20–30 cases under the guidance of experienced surgeon; however, at least 50 cases are required in the absence of guidance, and even with the experience of more than 80 cases, there were 25% of patients developing incontinence (Endo et al, ). In addition, older age, larger prostate volume, longer operative time and intra‐operative blood loss were also predictors of UI after AEEP (Hirasawa et al, ; Rausch et al, ; Xu et al, ).…”
Section: Evidence Synthesismentioning
confidence: 99%